Employees' perception towards career development system : a case study in Malaysia LNG, Bintulu - Lim, Ming Choo (Universiti Malaysia Sarawak, (UNIMAS), 2006)
The main purpose of this study is to determine the employees' perception towards career development system (CDS) in Malaysia LNG (MLNG), Bintulu. A self developed questionnaire was distributed to 350 employees in all the departments in MLNG but only 100 respondents were obtained. The overall reliability of the instrument was 0.930 on the Cronbach Alpha value. The findings show that 83% of the employees perceived organization's CDS positively and 17% of the respondents perceived CDS negatively. Four factors, namely training program, supervision, employees' motivation and compensation system were studied to determine their relationship with the employees' perception towards CDS. The results obtained from Pearson Correlation Coefficient Analysis show that all the four independent variables are positively related to the dependent variable. All independent variables show a moderately strong relationship with the dependent variable. However, the result of the regression analysis shows that compensation system is the most dominant factor that contributes to the employees' perception towards CDS. Independent sample T-test reveals that there is no significant difference between male and female in terms of their perception towards CDS. Similarly, one-way ANOVA test indicates that there is no difference among employees of various age groups and educational levels, in terms of their perception towards CDS. Based on the finding of this study, it is reasonable for MLNG to put more emphasize on the company's compensation system in order to form positive perception among the employees.